The COVID-19 catastrophe : what's gone wrong and how to stop it happening again - Horton, Richard C (Polity Press, 2020)
This publication focuses on the socio-political aspects of the COVID-19 pandemic, especially on the faulty response of local governments. Written for professionals and general public.
Keywords: Coronavirus Infections; veřejné zdravotnictví; National Health Programs; Sociological Factors; sociologické faktory; Risk Management; politologie, politika, zdravotní politika; řízení rizik; koronavirové infekce; COVID-19; Social Problems; Betacoronavirus; pandemie; sociální problémy; History, 21st Century; epidemiologické faktory; Epidemiologic Factors; Pandemics; dějiny 21. století; epidemiologie; programy národního zdraví